Challenges and Potential Solutions for Assessment Practice in Pentaksiran Tingkatan Tiga (Pt3) - Muhamad Firdaus Mohd Noh, Mohd Effendi @ Ewan Mohd Matore* (International Journal of Advanced Science and Technology, 2020)
The objective of high-stakes assessment is to appraise students’ achievement at the end of an academic calendar. Students’ result in the assessment is impactful in determining their future life such as a qualification for enrolment in university or job interviews. In operationalizing high-stakes assessment, standardization is an important element to ensure students are assessed with fairness and only based on their abilities. High-stakes assessment is normally administered by a centralised body without the involvement of students’ respective schools. However, the decision to assign students’ teachers as the sole examiner of high-stakes assessment is contentious whether teachers can adhere to standardization and measurement principles. Therefore, this paper aims to discuss the challenges faced by teachers when they are tasked to assess students in high-stakes assessment particularly in the context of Pentaksiran Tingkatan Tiga (PT3) in Malaysia and propose several potential solutions. The main idea underpinning this paper is to enhance the quality of assessment practice in education system which is salient to assure validity and reliability of results received by students. Such discussion is also needed to acknowledge teachers as a professional player in the arena of educational assessment. More importantly, the discussion in this paper puts forward an urge for educational stakeholders to redesign assessment system based on research-based practice.